Neuralgic Amyotrophy: A Rare Cause of Bilateral Diaphragmatic Paralysis. Issue 2 (3rd April 1998) - Shinder, Neil; Polson, Alasdair; Pringle, Elizabeth; O'Donnell, Denis E
Abstract : Neuralgic amyotrophy, also known as brachial neuritis, is a well described clinical entity. Diaphragmatic dysfunction, as a result of phrenic nerve root involvement (cervical roots 3 to 5), is an uncommon, but increasingly recognized association. The case of a previously healthy 61-year-old woman who, after a prodrome of neck and shoulder discomfort, presented with severe orthopnea is described. Pulmonary function and electrophysiological studies led to a diagnosis of bilateral diaphragmatic paralysis. The patient's clinical course and the exclusion of other nerve entrapment syndromes and neurological disorders strongly favoured the diagnosis of neuralgic amyotrophy.